2004
DOI: 10.1097/00009957-200405000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of spastic diplegia in patients with cerebral palsy: Part II

Abstract: This review article describes the evaluation, treatment options, and expected outcomes for many of the common deformities of the lower extremities in patients with cerebral palsy. The evaluation tools including gait analysis will be applied to each specific deformity. Dynamic components are addressed with spasticity management and appropriate muscle and tendon procedures. The static components are treated with bony procedures, including various osteotomies and arthrodesis, incorporating biomechanical principle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 98 publications
0
15
0
3
Order By: Relevance
“…SEMLS is not a uniform procedure but is tailored to the child's needs and includes realigning bony levers, lengthening or transferring muscle-tendon units. 1 It has been demonstrated that SEMLS corrects musculoskeletal pathology and can significantly improve the gait pattern. 2,3 Most reports have described gait-related outcomes from the body structure and function domain.…”
mentioning
confidence: 99%
“…SEMLS is not a uniform procedure but is tailored to the child's needs and includes realigning bony levers, lengthening or transferring muscle-tendon units. 1 It has been demonstrated that SEMLS corrects musculoskeletal pathology and can significantly improve the gait pattern. 2,3 Most reports have described gait-related outcomes from the body structure and function domain.…”
mentioning
confidence: 99%
“…Aiona and Sussman [4] believed that the natural history of the spastic flatfoot begins with unbalanced muscles’ strength besides the subtalar joints, then contracture of the muscles causes skeletal changes like heel valgus and lateral displacement of the calcaneus. Upon further progression, secondary skeletal developmental malformation occurs complicated with osteoarthritis of the talocalcaneal joint, the talonavicular joint, and the metatarsophalangeal joint, thereby completely losing the potential of spontaneous relief.…”
Section: Introductionmentioning
confidence: 99%
“…Conservative treatments [4] include the use of insole, ankle-foot orthosis (AFO), and the use of assistive devices. Botulinum injection and baclofen pump therapy have also been tried.…”
Section: Introductionmentioning
confidence: 99%
“…Подход к оперативному лечению ортопедических осложнений ЦП заключается в выполнении многоуровневых одномоментных оперативных вмешательств [1,8,14,23,24,29,30]. В нашей серии 119 (87,5%) стоп имели вальгусную девиацию.…”
Section: Discussionunclassified